Development in the Digital Age: An Introduction to the Section. Issue 1 (31st March 2017) - Gilmore, Karen
ABSTRACT: The author highlights the massive cultural transformation of the 21st century as society moves into the technocultural age. The papers that follow represent a range of viewpoints about the impact of these changes on child development in the technocultural era, with special reference to the unique presentations of childhood symptomatology.